Enhancement of piezoelectric properties of Pb(Mg1/3Nb2/3)0.65Ti0.35O3ceramics by ZnO modification - Methee Promsawat (2018)
© 2017 Elsevier B.V. The effects of ZnO modification on the microstructure and piezoelectric properties of Pb(Mg1/3Nb2/3)0.65Ti0.35O3(PMNT) ceramics were investigated. The grain size tended to increase with increasing ZnO content. Secondary phases were observed in the ceramics with 4.0 and 11.0 mol%ZnO. The piezoelectric properties of the PMNT ceramics were enhanced by introduction of 0.4–4.0 mol%ZnO. The piezoelectric properties deteriorated when higher ZnO contents were used. Among all the investigated compositions, the highest piezoelectric performance was observed for the PMNT/0.4 mol%ZnO ceramic. This makes the PMNT/0.4 mol%ZnO ceramic promising for piezoelectric applications.